An investigation of acoustic deterrent devices to reduce cetacean bycatch in an inshore set net fishery - Hardy, Tom; Williams, Ruth; Caslake, Richard; Tregenza, Nick (J. Cetacean Res. Manage., 2023)
In Europe, problems with the use of pingers on larger fishing vessels have raised the question as to whether pingers would be practical on smaller vessels, which are a large proportion of the European static net fishing fleet. In this study, four netting vessels less than 10m long used AQUAmark pingers on part of their nets off the southwest coast of Britain over a 12 month period. Boat skippers recorded ease of use. Acoustic click detectors were deployed on test and control nets to assess the response of cetaceans to the pingers. No significant practical problems, apart from premature failure of pingers, were encountered. During the study, only one harbour porpoise was bycaught, in an unpingered net. In 650 days of acoustic data from pingered and non-pingered nets, matched by location, date and boat, there was a highly significant reduction in the number of porpoise clicks recorded at nets with pingers to 48% of the number predicted from the number recorded at control nets (range 35–51%). To assess habituation, single, modified pingers that were active for alternate seven hour periods were moored below a click detector at two sites, one of which has strong tides and high levels of associated ambient noise. This study showed a stronger pinger effect at the quiet site and a much reduced effect at the noisy site. There was evidence of a period of exclusion of porpoises following pinger use that could exceed seven hours, and no evidence of habituation. Results suggest that pingers are practical on small vessels, that they reduce harbour porpoise activity around nets and are therefore likely to reduce bycatch. Easier means of detecting pinger failure are needed. Pingers should be considered as a bycatch mitigation method in small vessel fisheries using bottom set nets.